Pengaruh Lama Stimulasi Listrik Dan Jenis Otot Terhadap Kandungan Air, pH Dan Cooking Loss Daging Sapi Pesisir - Arnim Arnim; Hilda Susanty (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The aims of the present research were to study the effect of time periods of electrics stimulation and muscle type on water content, pH and cooking loss of meat of pesisir cattle. This research was designed according to factorial attempt pattern 3 x 3 based on Randomized Block Design (RBD). The treatments were 3 levels of electric stimulated time, i.e. A1 = 1 minute, A2 = 2 minutes and A3 = 3 minutes as A factor, for the B factor is the muscle they are B1 = Longisimus dorsi, B2 = Supra spinatus and B3 = Biceps femoris. Results showed that water content of meat pesisir cattle ranged from 78.17 - 77.41 %, pH 6.03- 5.70 and cooking loss ranged from 42.31 - 37.96. The electric stimulated didn't give significant effect (P>0.05) on water content and pH, but cooking loss percentage decreased signtficantly (P<0.05) by increasing the time periods of electric stimulation time. Muscle type gave significant effect (P<0.05) on cooking loss.